The re-building effect of hurricanes: evidence from employment in the US construction industry - Eric Strobl; Frank A. Walsh (Institute for the Study of Labor (IZA), 2008)
We examine the impact of hurricane strikes on the construction industry in US counties. To this end we use a measure of hurricane destruction derived from a wind field model and historical hurricane track data and employ this within a dynamic labour demand framework. Our results show that destruction due to hurricanes causes on average an increase in country level employment in construction of a little over 25 per cent.
urn:nbn:de:101:1-20080619206
Keywords: J23; 330; Hurricanes; labour demand; construction industry; Sturm; Katastrophenschaden; Bauwirtschaft; Arbeitsnachfrage; Beschäftigungseffekt; Regionaler Arbeitsmarkt; USA